Impact of previous thoracic radiation therapy on the efficacy of immune checkpoint inhibitors in advanced non small cell lung cancer. (14th October 2020) - Hosokawa, Shinobu; Ichihara, Eiki; Bessho, Akihiro; Harada, Daijiro; Inoue, Koji; Shibayama, Takuo; Kishino, Daizo; Harita, Shingo; Ochi, Nobuaki; Oda, Naohiro; Hara, Naofumi; Hotta, Katsuyuki; et al.
Abstract: Objectives: Studies investigating the association between radiation therapy and the efficacy of immune checkpoint inhibitors in advanced non-small-cell lung cancer have provided inconsistent results, likely due to relatively small cohort sizes. This study investigated the effect of previous thoracic radiation therapy on the efficacy of immune checkpoint inhibitor therapy in a large non-small-cell lung cancer cohort. Patients and methods: We conducted a retrospective cohort study using data from 531 non-small-cell lung cancer patients who received monotherapy with programmed cell death protein 1/programmed death-ligand 1 inhibitors at nine institutions. The effects of thoracic radiation therapy on the efficacy of immune checkpoint inhibitors were investigated. Results: A total of 531 non-small-cell lung cancer patients treated with immune checkpoint inhibitors were included in this study. The progression-free survival period was significantly longer in patients that had received thoracic radiation therapy before immune checkpoint inhibitor therapy compared to those without previous thoracic radiation therapy (median progression-free survival 5.0 vs. 3.0 months, P = 0.0013). A multivariate analysis showed that thoracic radiation therapy was an independent predictive factor of improved progression-free survival (hazard ratio of progression-free survival: 0.79, P = 0.049). In contrast, extra-thoracic radiation therapy was associated with inferior outcomes (median progression-free survival 3.0 vs. 4.2 months, P = 0.0008). Conclusion: Previous thoracic radiation therapy, but not prior extra-thoracic radiation therapy, enhanced the efficacy of anti-programmed cell death protein 1/programmed death-ligand 1 therapy in non-small-cell lung cancer patients. Abstract : We investigated the effects of radiation therapy (RT) on the efficacy of immune checkpoint inhibitors in non-small-cell lung cancer patients and found that thoracic RT enhanced efficacy but extra-thoracic RT did not.